Pemanfaatan Reading Corner dalam Meningkatkan Kemampuan Literasi Membaca Peserta Didik di Sekolah Dasar - Lilis Amaliah Rosdiana; Dewi Kusuma (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2025)
This article aims to examine the implementation of reading corners in elementary schools and their impact on increasing literacy skills. The method used is a Systematic Literature Review (SLR) by analyzing twelve relevant scientific articles published in the last five years. The review process was conducted thru five stages: problem identification, setting inclusion and exclusion criteria, searching for articles using the keywords "reading corner," "reading corner," and "elementary literacy," data extraction, and thematic analysis. The study results show that reading corners have a significant positive impact on the cognitive, affective, and social aspects of students. The improvement in text comprehension skills, the growth of reading motivation, and the creation of a literacy culture in the school environment are the main benefits of an optimally managed reading corner. In addition, the role of teachers as literacy facilitators has proven to be very important in directing the effectiveness of the reading corner. Thus, the reading corner is not just a decorative element in the classroom, but a literacy strategy with great potential to cultivate a love for reading and improve the overall quality of primary education. Keywords: literacy; reading interest; students; reading corner, Abstrak Artikel ini akan mengkaji implementasi reading corner (reading corner) di sekolah dasar serta dampaknya terhadap peningkatan kemampuan literasi peserta didik. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan menganalisis dua belas artikel ilmiah yang relevan dan dipublikasikan dalam lima tahun terakhir. Proses kajian dilakukan melalui lima tahapan, yaitu identifikasi masalah, penetapan kriteria inklusi dan eksklusi, pencarian artikel menggunakan kata kunci “reading corner”, “reading corner”, dan “elementary literacy”, ekstraksi data, serta analisis tematik. Hasil kajian menunjukkan bahwa reading corner memberikan dampak positif yang signifikan dalam aspek kognitif, afektif, dan sosial peserta didik. Peningkatan kemampuan memahami teks, tumbuhnya motivasi membaca, serta terciptanya budaya literasi di lingkungan sekolah menjadi manfaat utama dari reading corner yang dikelola secara optimal. Selain itu, peran guru sebagai fasilitator literasi terbukti sangat penting dalam mengarahkan efektivitas reading corner. Dengan demikian, reading corner bukan sekadar elemen dekoratif dalam kelas, melainkan strategi literasi yang memiliki potensi besar dalam membentuk karakter gemar membaca dan meningkatkan kualitas pendidikan dasar secara menyeluruh. Katakunci: literasi; minat baca; peserta didik; reading corner